The impact of convective cold pool outflows on model biases in the Sahara. Issue 8 (26th April 2013) - Garcia‐Carreras, L.; Marsham, J. H.; Parker, D. J.; Bain, C. L.; Milton, S.; Saci, A.; Salah‐Ferroudj, M.; Ouchene, B.; Washington, R.
<x xml:space="preserve">Abstract</x> [1] Radiosonde data from Fennec supersite‐1 in the remote central Sahara have been used to evaluate the impact of convectively generated cold pool outflows on model errors. Model predictions are too warm and dry, with cold pools contributing significantly to the mean bias. Although dust concentrations are high within cold pools, the sign of the errors is inconsistent with radiative impacts of dust. Cold pools cause 29% of the meridional humidity flux, but this contribution is absent in the forecast and analysis. Assimilating radiosondes reduces the errors, but significant temperature and meridional humidity flux biases remain at night. The model biases are consistent with the larger‐scale heat low biases in the operational Met Office Unified Model and can be linked to known issues with convective parameterizations used in all global weather and climate models. This study suggests that the misrepresentation of moist convective processes can affect continental‐scale biases, altering the West African monsoon circulation.